Epileptic seizure detection by exploiting EEG signals using different decomposition techniques and machine learning approaches - Karim, Rezwanul; Nitol, Subah; Rahman, Md.Mushfiqur (BRAC University, 2019)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.